Haitian Agricultural Faculty Preparation for Their Academic Roles - Absalon Pierre; Marie Christelle Calixte; Kelly Moore; J. C. Bunch; Koenig; Lemâne Delva; T. Grady Roberts (Journal of International Agricultural and Extension Education, 2018)
Food insecurity is widespread in Haiti. The tertiary agricultureinstitutionshave the great challenge of educatingthe future professionals who will help in meeting the growth needs of the Haitian agriculturesector.The extent that faculty are prepared for the teaching roles is unknown. This study examined this topic using a basic qualitative study that consisted of interviews with 37 lecturers working at five leading agricultural universitiesin Haiti. Data were analyzed using a basic thematic analysis. Results revealed the majority of participants generally felt well-prepared for their academic roles. The institutional climate for professional development is variable across the universities represented by the participants of this study. Incentives for participating in professional development were primarily intrinsic. There were 56 specific topics suggested by participants for professional development trainings.
Keywords: professional development; higher education; Haiti; faculty